The Burden of Menstrual Migraine: Advances in diagnosis, treatment, and understanding of pathogenesis - Paulina Głogowska; Daria Furtak; Dawid Tulej; Alicja Dziedzic; Wiktor Grela; Jagoda Niewiadomska; Natalia Marko; Natalia Gniaź; Dominika Marciniuk; Aleksandra Górska (Journal of Education, Health and Sport)
Menstrual migraine is a debilitating neurological condition linked to hormonal fluctuations during the menstrual cycle. It disproportionately affects women of reproductive age, imposing significant personal and societal burdens. Characterized by intense, prolonged headaches often resistant to standard treatments, menstrual migraines are primarily triggered by estrogen withdrawal and further influenced by prostaglandins and neurotransmitter dysregulation. This review synthesizes current knowledge on the pathophysiology of menstrual migraine, emphasizing hormonal and genetic factors, and highlights diagnostic criteria distinguishing pure menstrual migraine from menstrually related migraine.